Optimalisasi Peran Bimbingan Konseling Islam Dalam Edukasi Hukum Keluarga Untuk Mengatasi Kekerasan Seksual, Kawin Paksa, Eksploitasi Ekonomi, Dan Menjamin Hak Anak - Chantika Rahmadhania; Royhan Ghifari; Aep Kusnawan; Sugandi Miharja (Khazanah Multidisiplin, 2025)
Sexual violence, forced marriage, and economic exploitation against women and children are forms of rights violations that have multidimensional impacts. This article examines the strategic role of Islamic Counseling Guidance (BKI) in family law education to address these issues and ensure the protection of children's rights. This study employs a descriptive qualitative approach through interviews, observations, and documentation of legal education workshop activities at MTT Al-Barakah Garut. Findings indicate that legal and religious literacy within families remains low, exacerbating risks of violence and structural injustice. BKI is deemed capable of integrating Islamic values and family law principles through a holistic approach—psychological, social, and spiritual. By targeting premarital counseling, family counseling, and fiqh education on child and women’s protection, BKI serves as an effective preventive and curative tool. This article suggests optimizing the BKI program as a sustainable educational strategy in efforts to create legally aware and violence-free families.